2011
DOI: 10.1590/s1808-18512011000200006
|View full text |Cite
|
Sign up to set email alerts
|

Escoliose idiopática do adolescente (eia): perfil clínico e radiográfico da lista de espera para tratamento cirúrgico em hospital terciário de alta complexidade do Sistema Público de Saúde Brasileiro

Abstract: OBJETIVO: Descrever através de estudo coorte transversal descritivo, os parâmetros clínicos e radiográficos dos pacientes portadores de escoliose idiopática do adolescente (EIA) que estão na lista de espera para tratamento cirúrgico eletivo em hospital universitário terciário de alta complexidade do Sistema Público de Saúde Brasileiro (SUS). MÉTODOS: Para definir o perfil clínico e radiográfico, coletamos os dados referentes à menarca, sexo, idade e dados radiográficos (sinal de Risser, ângulo de Cobb, Nash-Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
(21 reference statements)
2
16
0
9
Order By: Relevance
“…22 Neto et al 23 studied 170 patients with spinal deformities waiting for surgical procedures in a tertiary hospital school in the Brazilian public system and they observed a predominance of congenital and neuromuscular deformities, mainly among the female patients. Lima Júnior et al 24 in a study of adolescents with idiopathic scoliosis in the same hospital service perceived that of the 51 patients, 42 were females with an average age of 15 years. The average value of the principal curve was 60 degrees and the average wait time for surgery was 25 months.…”
Section: Discussionmentioning
confidence: 99%
“…22 Neto et al 23 studied 170 patients with spinal deformities waiting for surgical procedures in a tertiary hospital school in the Brazilian public system and they observed a predominance of congenital and neuromuscular deformities, mainly among the female patients. Lima Júnior et al 24 in a study of adolescents with idiopathic scoliosis in the same hospital service perceived that of the 51 patients, 42 were females with an average age of 15 years. The average value of the principal curve was 60 degrees and the average wait time for surgery was 25 months.…”
Section: Discussionmentioning
confidence: 99%
“…Other Brazilian studies have shown similar results. [ 15 17 ] Waiting lines for procedures within these specialties have long been a reality in several regions of the country. Our research describes the current health status of the population in the Manaus metropolitan region and the pent-up demand for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Júnior et al, 22 as mulheres apresentam maior magnitude da curva da coluna vertebral e é necessária intervenção cirúrgica para impedir sua progressão.…”
Section: Discussionunclassified